Pendekatan dan Media Pembelajaran Bahasa Indonesia dalam Implementasi Permendikbud No. 103 Tahun 2014 di Kelas 5 Sekolah Dasar - Endang Nur Azizah; Fathan Faqih Ali; Hanifah Nur Azizah; Nanda Oktavia; Rissa Alivia Zahra; Sayyidah Az-zahra; Mayarni Mayarni (CV. Alim's Publishing, 2024)
This study explores the urgency of improving the quality and effectiveness of teaching and learning processes in primary schools through the use of varied learning approaches and media. With the aim of analyzing the relationship of these methods and media to students' motivation, concept understanding, learning style accommodation, critical thinking skills development and social interaction, this study uses qualitative methods. The study also ensures that the implementation of these learning strategies is in accordance with the standards of Permendikbud No. 103 of 2014. The results show that education providers are expected to adopt learning methods that have a positive impact on increasing interest and motivation, facilitating concept understanding, accommodating different learning styles, and encouraging critical thinking skills and social interaction. The use of creative and varied learning media is also emphasized, allowing students to understand concepts through visual demonstration or practical experience. In conclusion, learning methods and media variations fulfill the expectations of Permendikbud No. 103 of 2014, providing students with interactive, inspiring, fun, challenging and meaningful learning experiences.